Faith in the Future : Understanding the Revitalization of Religions and Cultural Traditions in Asia. - Reuter, Thomas (Social sciences in Asia., 2012)
Revitalization of religious and cultural traditions is taking place in nearly all contemporary Asian societies and beyond. Faith in the Future: Understanding the Revitalization of Religions and Cultural Traditions in Asia provides a comparative analysis of the key features and aspirations of revitalization movements and assesses their scope for shaping the future trajectories of societies in all parts of the world.